The Effect of Differentiation Learning Strategies on Student Learning Results - Parlindungan Sitorus; Eka Notasya Simanullang; Andriono Manalu; Indah Septa Ayu Laia; Riossally Marselina Tumanggor; Juliper Nainggolan (Jurnal Penelitian Pendidikan IPA, 2022)
The research conducted in the even semester of the 2021/2022 academic year aims to see how the influence of different learning strategies on the learning results of eighth-grade students of State Junior High School 4 Medan on vibration and wave material. This study used true experimental research with a pretest posttest control group design. The population used in this study was class VIII of State Junior High School 4 Medan as a whole consisting of 346 people. The sample of this study was class VIII-2 as the experimental class and VIII-3 as the control class selected using the cluster random sampling technique. To find out student learning results, multiple-choice questions with a total of 20 items have been previously tested for validity, reliability, difficulty, and discrimination. The learning results of the two classes were tested for normality with the Lilliefors test and the homogeneity test using the F test. Then a one-sided t-test was carried out for = 0.05, obtained tcount = 2.07 > ttable = 1.6697. As for the regression test obtained = 15.79 + 0.78X. Based on the results of the study, it can be concluded that there is an influence of differentiation learning strategies on the learning results of grade VIII students of State Junior High School 4 Medan.